2019
DOI: 10.1002/jcla.22998
|View full text |Cite
|
Sign up to set email alerts
|

Circulating plasma circular RNAs as novel diagnostic biomarkers for congenital heart disease in children

Abstract: ObjectiveThe diagnostic value of circulating circular RNAs (circRNAs) has received more and more attention. However, little has been reported about their potential in the diagnosis of congenital heart diseases (CHD). In this study, we explored differential expression of circRNAs from children with CHD to evaluate their potential as clinical biomarkers.MethodsWe established a discovery cohort (four CHD cases; four matched healthy controls) and a validation cohort (40 CHD cases; 40 matched healthy controls). Mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 38 publications
0
30
2
Order By: Relevance
“…A study including 40 children with CHD (namely VSD and ASD) and 40 healthy children identified 10 upregulated and 157 downregulated circRNAs in the plasma of the CHD group. Validation by qPCR demonstrated three circRNAs, hsa_circRNA_004183, hsa_circRNA_079265, and hsa_circRNA_105039, to be significantly decreased in the affected group [90]. Hsa_circRNA_105039 presented the best diagnostic value with a sensitivity of 80%, a specificity of 100%, and AUC of 0.907, but altogether, the three circRNAs had an AUC of 0.965, suggesting a combinatorial approach to be effective in the diagnosis of CHD [90].…”
Section: Congenital Heart Defectsmentioning
confidence: 96%
“…A study including 40 children with CHD (namely VSD and ASD) and 40 healthy children identified 10 upregulated and 157 downregulated circRNAs in the plasma of the CHD group. Validation by qPCR demonstrated three circRNAs, hsa_circRNA_004183, hsa_circRNA_079265, and hsa_circRNA_105039, to be significantly decreased in the affected group [90]. Hsa_circRNA_105039 presented the best diagnostic value with a sensitivity of 80%, a specificity of 100%, and AUC of 0.907, but altogether, the three circRNAs had an AUC of 0.965, suggesting a combinatorial approach to be effective in the diagnosis of CHD [90].…”
Section: Congenital Heart Defectsmentioning
confidence: 96%
“…With the use of advanced technologies in sequencing and data analysis, a lot of circRNAs have been detected in human hearts and been reported to be associated with CVD ( Jakobi et al, 2016 ; Werfel et al, 2016 ; Fan et al, 2017 ; Tan et al, 2017 ) ( Table 2 and Figure 2 ). Moreover, circRNAs have been observed to have great potential as biomarkers for the diagnosis and prognosis of CVD ( Vausort et al, 2016 ; Sonnenschein et al, 2019 ; Wu et al, 2019 ; Vilades et al, 2020 ) ( Table 3 and Figure 2 ).…”
Section: Circrnas and Cardiovascular Diseasesmentioning
confidence: 99%
“…Moreover, circTMEM56 and circDNAJC6 could be indicators of disease severity in patients with HCM ( Sonnenschein et al, 2019 ). Wu et al (2019) reported three notably downregulated circRNAs (hsa_circRNA_004183, hsa_circRNA_079265 and hsa_circRNA_105039) in the plasma of children with congenital heart diseases (CHD) and employed ROC analyses to determine their potential to be biomarkers. They found the great potential of three circRNAs as novel non-invasive diagnostic biomarkers for CHD ( Wu et al, 2019 ).…”
Section: Circrnas As Biomarkers For Cvdmentioning
confidence: 99%
See 1 more Smart Citation
“…A study from 2019 established a circRNA-miRNA-mRNA network and identified circYOD-1 as a circulating biomarker for coronary artery disease ( Miao et al, 2019 ). A study by Wu et al (2019) identified three differentialy regulated circRNAs in pediatric patients with congenital heart disease: hsa_circRNA_004183, hsa_circRNA_079265 and hsa_circRNA_105039. Another study reported several circRNAs linked to hypertrophic cardiomyopathy (HCM) in humans.…”
Section: Circrnas In Cvdmentioning
confidence: 99%